1996
DOI: 10.23986/afsci.72754
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide evolution from snow-covered agricultural ecosystems in Finland

Abstract: The release of CO2 from the snow surface in winter and the soil surface in summer was directly or indirectly measured in three different soil types (peat, sand and clay) in agricultural ecosystems in Finland. The closed chamber (CC) method was used for the direct and Pick’s diffusion model (DM) method for the indirect measurements. The winter soil temperatures at 2-cm depth were between 0 and 1°C for each soil type. The concentration of CO2 within the snowpack increased linearly with snow depth. The average fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“… Koizumi et al [1996] reported CO 2 fluxes of a nearly equal magnitude to ours, about 8 μg CO 2 m −2 s −1 , in practically the same peat soil as ours using the snow gradient and closed chamber method. In agricultural sandy and clay soils the CO 2 production rates were smaller, ranging from 3 to 6 μg CO 2 m −2 s −1 [ Koizumi et al , 1996]. In a peat soil grassland in eastern Finland, clearly higher wintertime emissions of 2.9 g CO 2 m −2 d −1 , equivalent to 34 μg CO 2 m −2 s −1 , have been measured with the chamber technique [ Alm et al , 1999].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“… Koizumi et al [1996] reported CO 2 fluxes of a nearly equal magnitude to ours, about 8 μg CO 2 m −2 s −1 , in practically the same peat soil as ours using the snow gradient and closed chamber method. In agricultural sandy and clay soils the CO 2 production rates were smaller, ranging from 3 to 6 μg CO 2 m −2 s −1 [ Koizumi et al , 1996]. In a peat soil grassland in eastern Finland, clearly higher wintertime emissions of 2.9 g CO 2 m −2 d −1 , equivalent to 34 μg CO 2 m −2 s −1 , have been measured with the chamber technique [ Alm et al , 1999].…”
Section: Resultssupporting
confidence: 79%
“…Fluxes from our site were smaller than those measured with a snow gradient method in a sandy loam soil growing barley in Canada, where the respiration rate from the snow‐covered, unfrozen soil ranged from 15 to 78 μg CO 2 m −2 s −1 in February and March 1994–1997 [ van Bochove et al , 2000]. Koizumi et al [1996] reported CO 2 fluxes of a nearly equal magnitude to ours, about 8 μg CO 2 m −2 s −1 , in practically the same peat soil as ours using the snow gradient and closed chamber method. In agricultural sandy and clay soils the CO 2 production rates were smaller, ranging from 3 to 6 μg CO 2 m −2 s −1 [ Koizumi et al , 1996].…”
Section: Resultsmentioning
confidence: 99%
“…However, these winter CO2 fluxes from barley were higher than those (2.8 to 7.5 [tg CO2 m -2 s 'l) estimated under snow cover from barley plots in Finland [Koizumi et al, 1996]. Interannual variations of CO 2 fluxes do not …”
Section: Interannual Variationsmentioning
confidence: 57%
“…During the snow covered season in 2004, ecosystem respiration was measured with the snow‐gradient method (Sommerfeld et al, 1993; Koizumi et al, 1996; Alm et al, 1999; Maljanen et al, 2004) from the same sampling locations as those during the snow free period. Gas samples of 20 ml were taken from the depth of 10–20 cm below the snow surface with gas‐tight plastic syringes (Terumo Europe, Leuven, Belgium), attached to a 3.2 mm diameter metal pipe.…”
Section: Methodsmentioning
confidence: 99%